Identities involving harmonic numbers that are of interest for physicists - Prodinger, Helmut (Utilitas Mathematica, 2010)
We treat a class of combinatorial sums considered by Vermaseren [8] with an elementary approach. The resulting evaluations are in terms of (generalized) harmonic numbers.